trig
posted by Abe .
eliminate the parameter t from the following
x = 4 sin t y= 7 cos t
sketch the graph

trig 
Reiny
t = sin^{1} (x/4)
do the t for the other equation the same way, then equate the two results.
to graph it, I would stick with the original equations, and substitute some critical values for t such as 30,45,60,90ยบ or pi/6,pi/4,pi/3,pi/2 etc if you are in radians.
Respond to this Question
Similar Questions

trig
Reduce the following to the sine or cosine of one angle: (i) sin145*cos75  cos145*sin75 (ii) cos35*cos15  sin35*sin15 Use the formulae: sin(a+b)= sin(a) cos(b) + cos(a)sin(b) and cos(a+b)= cos(a)cos(b)  sin(a)sin)(b) (1)The quantity … 
tigonometry
expres the following as sums and differences of sines or cosines cos8t * sin2t sin(a+b) = sin(a)cos(b) + cos(a)sin(b) replacing by by b and using that cos(b)= cos(b) sin(b)= sin(b) gives: sin(ab) = sin(a)cos(b)  cos(a)sin(b) … 
math
Eliminate the parameter (What does that mean? 
TRIG!
Posted by hayden on Monday, February 23, 2009 at 4:05pm. sin^6 x + cos^6 x=1  (3/4)sin^2 2x work on one side only! Responses Trig please help!  Reiny, Monday, February 23, 2009 at 4:27pm LS looks like the sum of cubes sin^6 x + cos^6 … 
trig
The expression 4 sin x cos x is equivalent to which of the following? 
Math
Eliminate the parameter and write the corresponding rectangular equation whose graph represents the curve. x = secQ Y = tanQ Would I use cos^2Q + sin^2Q = 1? 
Math
Eliminate the parameter and write the corresponding rectangular equation whose graph represents the curve. x = sec Q y = cos Q x^2 + y^2 = 1/cos^2 + sin^2/cos^2 = x^2(1 +sin^2) = x^2(2cos^2) x^2(21/x^2) = 2x^2  1 x^2  y^2 = 1 My … 
trig
I don't understand this. can you please tell how you got each answer? 
trig function
Suppose f(x)=cos x  sin x and g(x)=cos x + sin x. Explain why the graph of (fxg)(x) is equivalent to the graph of h(x)=cos x after it has been horizontally compressed by a factor of 1/2. Thanks so much... 
trig function
Suppose f(x)=cos x  sin x and g(x)=cos x + sin x. Explain why the graph of (fxg)(x) is equivalent to the graph of h(x)=cos x after it has been horizontally compressed by a factor of 1/2. Please help, thank you!